Efektifitas Oral Hygiene terhadap Jumlah Koloni Mikroba sebagai Risiko Ventilator Associated Pneumonia (VAP) - Ahmad Syarif; Eko Winarto; Julvainda Eka P.U; Fery Agusman; Amrih Widiati (Poltekkes Kemenkes Padang, 2024)
Ventilator Associated Pneumonia (VAP) is inflammation of the lung parenchyma when a patient receives mechanical ventilation for more than 48 hours, caused by the bacteria Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumannii, Staphylococcus aureus, and Escherichia coli. The aim of the research was to determine the effectiveness of oral hygiene between chlorhexidine gluconate 0.2% and Povidone Iodine 1% on the number of microbial colonies as a risk of VAP. The research design is True Experiment Design in the form of Pretest-Posttest Control Group Design. The population is patients on mechanical ventilation from February to March 2024. The number of samples was 15 in each experimental and control group determined randomly. The research variable is counting the number of microbial colonies through swab culture and carrying out the paired sample t-test and dependent sample t-test. The research showed that there was a significant difference (P=0.000) in the pre-test with the number of microbial colonies being greater than the post-test in each chlorhexidine gluconate 0.2% group (difference in mean value 63.13) and the povidone iodine 1% group (difference in average value 71,922) for all microbes. Chlorhexsidine Gluconate 0.2% is more effective than Povidone Iodine 1% with a significant difference in the number of microbial colonies (average p-value > 0.05) both in the pre-test (difference in average value 25,198) and post-test (difference in average value average 16.46) on all microbes. Oral hygiene using chlorhexidine gluconate 0.2% is more effective than povidone iodine 1% on the number of microbial colonies as a risk of VAP. Recommended to optimize the use of 0.2% chlorhexidine gluconate in the cleaning of medical instruments such as ventilators.